Exploring the impact of scientific advancements on hadith commentaries - Sevdenur Alhattab; Khairil Husaini Jamil (Penerbit Universiti Kebangsaan Malaysia, 2024)
This article examines the complex relationship between scientific advances and the interpretation/commentary of hadith, or the sayings and actions of Prophet Muhammad in Islam. The historical context of hadith commentaries is investigated, with a focus on the evolution of interpretive traditions from simple explanations to comprehensive works. The research ultimately focuses on the paradigm shift in hadith commentary influenced by early modern reformist orientations that sought to reconcile Islamic teachings with contemporary scientific knowledge. A case study examines the emergence of scientific interpretation by analysing a hadith from Sahih Muslim in light of modern scientific understanding. The article discusses the difficulties and controversies surrounding the integration of scientific data into hadith commentaries, emphasizing the dynamic nature of science as well as the distinct epistemological origins of hadith and science. It concludes by proposing a dynamic approach to the study of hadith and its commentaries, allowing for the re-evaluation of approaches in light of evolving scientific knowledge.